Urbanization indices development and use in the coastal ecological realm: a review - Marlow, Bailey N.; Griffen, Blaine D. (Frontiers in Ecology and Evolution, 2025)
Human populations are moving to coastal regions at a rapid pace, and growing populations are creating large impacts on ecological systems through the development of infrastructure and resource use. Urbanization indexes (UI) are used for a wide range of purposes related to understanding how urban growth impacts both urban development and ecological systems. Most UIs are developed using different factors, and there is a lack of standardization across studies even within the same study system. We reviewed the existing literature that utilizes a UI in the context of ecological questions within coastal regions to determine their utility in assessing how ecological impacts vary across coastal environments and are useful in identifying how urban growth is affecting ecosystems and species. We found that existing variation in UI development hampers the ability to make comparisons across studies and systems. To more fully understand the impacts of urbanization we recommend that UIs used in future studies be standardized to facilitate comparisons across time and studies. We offer guidance on how this can be done.